Corneal flap thickness with the Moria M2 single-use head 90 microkeratome in 72 consecutive LASIK procedures - Karabela Y (Dove Medical Press, 2017)
Yunus Karabela,1 Orkun Muftuoglu,2 Faruk Kaya1 1Department of Ophthalmology, Medipol University, 2Department of Ophthalmology, Vehbi Koç Vakfi Amerikan Hospital, Istanbul, Turkey Purpose: This study aimed to evaluate the accuracy and consistency of corneal flap thickness in laser-assisted in situ keratomileusis (LASIK) with the Moria M2 single-use head 90 microkeratome. Methods: The central corneal thickness of 72 (37 right, 35 left) eyes of 37 patients was measured by ultrasonic pachymetry preoperatively and intraoperatively after flap cut. The Moria M2 single-use head 90 microkeratome was used to create a superior hinged flap in all eyes. The right eyes were always operated on before the left eyes in each patient, using the same blade in all bilateral cases. All patients underwent LASIK for myopia and/or myopic astigmatism using VISX Star S4 platform. Results: The mean preoperative spherical equivalent refraction was -3.55±2.30 D (range: -0.625 to -11.00 D), preoperative central corneal thickness by ultrasonic pachymetry was 541±26.82 µm (490–600 µm) and steepest K was 44.08±1.49 D (40–46.75 D) in all eyes. The mean flap thickness was 136.97±20.07 µm (106–192 µm), 131.2±19.5 µm (91–192 µm), and 134.16±19.85 µm (91–192 µm) in the right, left, and both eyes, respectively. A positive significant relationship was found between flap thickness and preoperative ultrasonic pachymetry thickness. No significant relationship was found between flap thickness and the age, preoperative spherical equivalent, and preoperative steepest K. The difference between the first and second eyes was not significant. There were no major intraoperative and postoperative complications in all eyes. Conclusion: The Moria M2 single-use head 90 microkeratome cut relatively thicker flaps than were intended. The flap thickness range was quite wide. This was a disadvantage for the accuracy and consistency of corneal flap thickness. Keywords: flap thickness, laser-assisted in situ keratomileusis, LASIK, microkeratome, Moria M2 single-use head